Canagliflozin attenuates the progression of atherosclerosis and inflammation process in APOE knockout mice - Νarjes Nasiri-Ansari (Cardiovascular Diabetology, 2018)
Abstract Background Sodium glucose co-transporter2 inhibitors reduce the incidence of cardiovascular events in patients with type 2 diabetes mellitus based on the results of recent cardiovascular outcome studies. Herein, we investigated the effects of long-term treatment with canagliflozin on biochemical and immunohistochemical markers related to atherosclerosis and atherosclerosis development in the aorta of apolipoprotein E knockout (Apo-E(−/−)) mice. Methods At the age of 5 weeks, mice were switched from normal to a high-fat diet. After 5 weeks, Apo-E(−/−) mice were divided into control-group (6 mice) treated with 0.5% hydroxypropyl methylcellulose and Cana-group (7 mice) treated with canagliflozin (10 mg/kg per day) per os. After 5 weeks of intervention, animals were sacrificed, and heart and aorta were removed. Sections stained with hematoxylin–eosin (H&E) were used for histomorphometry whereas Masson’s stained tissues were used to quantify the collagen content. Immunohistochemistry to assess MCP-1, CD68, a-smooth muscle actin, MMP-2, MMP-9, TIMP-1 and TIMP-2 expression was carried out and q-PCR experiments were performed to quantify mRNA expression. Results Canagliflozin-group mice had lower total-cholesterol, triglycerides and glucose levels (P < 0.01), while heart rate was significantly lower (P < 0.05). Histomorphometry revealed that one in seven Cana-group mice versus four in six control mice developed atheromatosis, while aortic root plaque was significantly less, and collagen was 1.6 times more intense in canagliflozin-group suggesting increased plaque stability. Immunohistochemistry revealed that MCP-1 was significantly less expressed (P < 0.05) in the aortic root of canagliflozin-group while reduced expression of a-actin and CD68 was not reaching significance (P = 0.15). VCAM-1 and MCP-1 mRNA levels were lower (P = 0.02 and P = 0.07, respectively), while TIMP-1/MMP-2 ratio expression was higher in canagliflozin-group approaching statistical significance (P = 0.07). Conclusions Canagliflozin attenuates the progression of atherosclerosis, reducing (1) hyperlipidemia and hyperglycemia, and (2) inflammatory process, by lowering the expression of inflammatory molecules such as MCP-1 and VCAM-1. Moreover, canagliflozin was found to increase the atherosclerotic plaque stability via increasing TIMP-1/MMP-2 ratio expression.